Evaluation of Pilot Ladder Safety Systems Using a Checklist Approach: Case Study on MV Westerdam and MV Hao Qiang 57 at Tanjung Perak Port - Narko, Narko; Wahyudi, Slamet Imam; Sulistyo, Juny Andry (ASTONJADRO, 2026)
Pilot ladder operations are a critical component of pilotage services and inherently involve high safety risks. Although international standards such as SOLAS and ISO 799-1 provide strict guidelines, accidents continue to occur due to technical limitations, human factors, and managerial deficiencies. This study assesses the pilot ladder safety systems on Cruise Ship MV Westerdam and Cargo Ship MV Hao Qiang 57 at Tanjung Perak Port. A descriptive qualitative approach was employed using a safety checklist, short interviews, and limited observations, focusing on six aspects: ladder condition, safety fittings, lighting, cleanliness, usage, and maintenance. The results show that MV Westerdam achieved full compliance (100%) with all safety standards, supported by complete maintenance records and regular crew training. In contrast, the MV Hao Qiang 57 demonstrated only 70% compliance, with key deficiencies in the availability of safety harnesses, updated crew training, and maintenance documentation. These findings indicate that pilot ladder safety cannot be ensured solely through the physical conditions of the ladder but requires an integrated approach encompassing technical, human, and managerial dimensions. MV Westerdam illustrates best practices in implementing safety systems, while MV Hao Qiang 57 highlights critical areas for improvement. Overall, this study provides both theoretical contributions to maritime safety literature and practical recommendations for enhancing safety systems in Indonesian ports.